Gender dan Kepuasan Keuangan Investor Pasar Modal di Sulawesi Selatan - Ayu Parmitasari, Rika Dwi Ayu Parmitasari (Patria Artha University, 2017)
Â Every individual will try to get happiness in life that is supported one of them with financial satisfaction. One of the ways in achieving financial satisfaction is through investment behavior and investment container available is capital market. This study discusses the financial satisfaction of capital market investors and their relation to gender. The study found that the majority of investors, both male and female, have relatively good financial satisfaction. In other words, capital market investments are valued to provide the ability to meet the needs and increase the assets. Through discriminant analysis and different tests, the results show that the financial satisfaction of male and female investors differs significantly